Piezocatalytic Tumor Therapy by Ultrasound-Triggered and BaTiO3 -Mediated Piezoelectricity - Zhu, Piao (Advanced materials (Deerfield Beach, Fla.), 2020)
© 2020 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.